Development of fed-batch strategy to produce bacteria cellulose - Chua, Gek Kee; Soo, Yang Kee (Akademi Sains Malaysia, 2023)
Bacteria Cellulose (BC) is a type of biopolymer widely used in areas such as biomedicine and paper manufacturing industries. The batch fermentation mode of BC is less cost-effective as the yield is low. This study aims to determine the best fed-batch cultivation strategy to produce BC of high yield and quality. First, batch fermentation mode was carried out to determine the glucose consumption profile of Gluconacetobacter xylinus using Yeast Extract Glucose Chloramphenicol Medium (YGC). By using the information, the fed-batch strategies with feeding frequencies of 1 time and 3 times per 14-day total fermentation period and varied feed composition (YGC medium and pure glucose solution) were set up. The yield, water holding capacity, morphology, and strength of BC were monitored. It is found that BC produced from fed-batch modes has a higher yield (3.75 g/L for low feed frequency and 4.79 g/L for high feed frequency) compared to batch mode (2.24 g/L). The BC produced with pure glucose solution has the highest water holding capacity (87.34 g water/g sample) among the different modes. The FE-SEM micrographs showed that BC produced in the high feeding frequency with YGC medium fed-batch mode has the highest microfibril density and, thus, the best mechanical strength from this mode. To conclude, the fed-batch mode with higher feeding frequency (3 days intervals for a total of 14 days) using YGC medium has the best BC yield and quality.